2021
DOI: 10.31557/apjcp.2021.22.12.4051
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Tobacco Smoking on Health-Related Quality of Life among Saudi Adolescents During the COVID-19 Pandemic

Abstract: Objective: This study aimed to evaluate the impact of cigarette smoking and health-related quality of life among Saudi secondary vocational students during the COVID-19 pandemic. Methods: A convenience sample of 328 answered a web-based self-administered questionnaire based on the Youth Risky Behavior Monitoring System (YRBSS) plus the Short Form 12 (SF-12) were included in the study. The target population included all Saudi students enrolled at the Secondary Industrial Institute in Dammam, Saudi Arabia, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…A recent study showed that one who smoke has a chance to develop anxiety during COVID-19 lockdown (Tareke et al, 2022). Therefore, the mental health dimension of quality of life of smoker should be decreased during pandemic and this result is concordant with the observation by Al Kalif et al, (2021).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…A recent study showed that one who smoke has a chance to develop anxiety during COVID-19 lockdown (Tareke et al, 2022). Therefore, the mental health dimension of quality of life of smoker should be decreased during pandemic and this result is concordant with the observation by Al Kalif et al, (2021).…”
supporting
confidence: 57%
“…
We read the article entitle "The Negative Impact of Tobacco Smoking on Health-Related Quality of Life among Saudi Adolescents During the COVID-19 Pandemic (Al Kalif et al, 2021)." Al Kalif et al, (2021) concluded that "The results indicate that smoking has a negative impact on the quality of life of vocational students. Therefore, a health strategies plan may be developed to improve the quality of life for vocational students in Saudi Arabia."
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mass gatherings have been canceled, schools closed, Hajj pilgrimage has been restricted, curfews have been imposed, and localities have been locked down due to increased transmission [26,27]. Health-related quality of life (HRQoL) is an essential component of public health monitoring and physical and mental health [22]. Often survivors of COV-ID-19 may develop post-COVID-19 syndrome affecting physical, cognitive, or mental functions [1,2,5,28].…”
Section: N Discussionmentioning
confidence: 99%
“…Health-related quality of life was assessed using the RAND-12 item Short Form Health Survey (SF12) scale. We used the translated version to the Arabic language from a Saudi study that used the HRQoL RAND-12 tool [22]. These include physical function (PF), physical role (RP), physical pain (BP), general health (GH), vitality (VT), social function (SF), role emotion (RE), and mental health (MH).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%